Blended biomass pellets as fuel for small scale combustion appliances: Effect of blending on slag formation in the bottom ash and pre-evaluation options. (15th January 2018) - Zeng, T.; Pollex, A.; Weller, N.; Lenz, V.; Nelles, M.
Highlights: Blending of herbaceous and woody biomass was employed to reduce bottom ash slagging. More than 70 wt% wood is required to avoid severe bottom ash slagging. Ternary diagrams can be advantageous for a pre-evaluation of bottom ash slagging. Abstract: Non-woody biomass fuels have a great potential to replace fossil fuels and reduce greenhouse gas emissions. At the same time, their application in small scale combustion appliances for heat production is often associated with increased operational problems (e.g. slagging in the bottom ash or deposit formation) as well as elevated gaseous and particulate matter emission levels. To mitigate these problems, scope and limitation of blending raw materials owing critical fuel composition with less problematic biomasses have been systematically studied during combustion experiments in a commercially available small scale combustion appliance with a nominal heat capacity of 30 kW. Three pellet batches of pure biomass (i.e. pine wood, miscanthus and wheat straw) and seven blended biomass pellet batches have been employed. Slag formation in the bottom ash as well as amount of agglomerated bottom ash particles were monitored and evaluated with respect to the determined ash melting temperatures and the measured fuel bed temperatures. Significant reduction of the slagging risk in the bottom ash during combustion of herbaceous fuels can only be achieved for high blending ratios with more than 70 wt% wood. It was furthermore studied to which extent fuel indices are applicable for the prediction of the bottom ash behavior of blended biomass fuels. Furthermore, ternary diagrams were used to rationalize the observed slagging characteristics. It was found that ternary diagrams are superior for a pre-evaluation of the slagging risk in the bottom ash to fuel indices alone. With the knowledge of the fuel ash composition and the ash melting temperatures, a well based pre-evaluation of utilization options can be performed.